2019
DOI: 10.1111/jcmm.14771
|View full text |Cite
|
Sign up to set email alerts
|

CBX4 promotes the proliferation and metastasis via regulating BMI‐1 in lung cancer

Abstract: Proliferation and metastasis are significantly malignant characteristics of human lung cancer, but the underlying molecular mechanisms are poorly understood. Chromobox 4 (CBX4), a member of the Polycomb group (PcG) family of epigenetic regulatory factors, enhances cellular proliferation and promotes cancer cell migration. However, the effect of CBX4 in the progression of lung cancer is not fully understood. We found that CBX4 is highly expressed in lung tumours compared with adjacent normal tissues. Overexpres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 43 publications
(102 reference statements)
0
42
0
Order By: Relevance
“…CBX4 belongs to the Polycomb group (PcG) family and revealed to promote lung cancer proliferation and metastasis through recruiting BMI-1, indicating CBX4 may be a possible therapeutic target in cancer. 19 Moreover, CBX4 was revealed to exert oncogenic roles in breast cancer progression via affecting the Notch1 signaling pathway. 20 In our studies, we found lncRNA FOXP4-AS1 upregulates CBX4 expression via miR-136-5p.…”
Section: Discussionmentioning
confidence: 99%
“…CBX4 belongs to the Polycomb group (PcG) family and revealed to promote lung cancer proliferation and metastasis through recruiting BMI-1, indicating CBX4 may be a possible therapeutic target in cancer. 19 Moreover, CBX4 was revealed to exert oncogenic roles in breast cancer progression via affecting the Notch1 signaling pathway. 20 In our studies, we found lncRNA FOXP4-AS1 upregulates CBX4 expression via miR-136-5p.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al [13], Han et al [17] and Chang et al [11] also found CBX3 to be overexpressed in NSCLC, and Zhou et al [13] further confirmed that CBX3 is an independent prognostic biomarker for NSCLC. In the study by Hu et al [18], CBX4 had been shown to be overexpressed in lung cancer compared with adjacent normal tissues. CBX5 is proved to be up-regulated in LUAD compared with nontumorous lung tissues in the study of Yu et al [19], and its overexpression is associated with shorter OS.…”
Section: Discussionmentioning
confidence: 96%
“…Aberrant expression and prognostic significance of CBX4 has been documented in several human malignancies including liver cancer, colorectal cancer, and breast cancer as well as lung cancer [ 27 , 29 , 45 , 46 ]. In fact, during the course of the present study, Hu et al independently reported the ability of CBX4 to promote the proliferation and metastasis in lung cancer [29] . Of note, the in vivo validation in their study was performed using xenografts of established human lung cancer cell lines in nude mice.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that the role of CBX4 is tissue-dependent and varies with the type of malignancy. Using established human lung cancer cell lines, Hu et al recently reported that CBX4 promotes the proliferation and metastasis in lung cancer [29] , supporting a cancer-promoting role for CBX4 in lung cancer. While given the significant differences among distinct histologic subtypes of lung cancer and between cell model-based and animal model-based in vivo studies, whether CBX4 plays a role in the initiation and development of autochthonous LUAD tumors in vivo has yet to be determined.…”
Section: Introductionmentioning
confidence: 91%